2018
DOI: 10.15789/1563-0625-2018-4-463-476
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Regulation of Basic Physiological and Pathological Processes

Abstract: Резюме. В последние годы ведется активное изучение значимости пуринергического сигналинга в патогенезе широкого спектра заболеваний и патологических состояний, к числу которых относятся регуляция инфекционного и неинфекционного воспаления, опухолевого роста и метастазирования, реакций отторжения трансплантата, аутоиммунных заболеваний, кальцификации элементов сердечно-сосудистой системы и т.д. Было показано, что пуринергическая система осуществляет тонкую регуляцию функций клеток иммунной системы аналогично ци… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 99 publications
0
3
0
1
Order By: Relevance
“…Previously, it was demonstrated that purinergic signaling played an important role in regulating T-cell functions (Ledderose et al, 2016; Golovkin et al, 2018). T cells migrating into the damaged heart tissues upregulate enzymatic machinery for degrading extracellular ATP and NAD to adenosine (Borg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was demonstrated that purinergic signaling played an important role in regulating T-cell functions (Ledderose et al, 2016; Golovkin et al, 2018). T cells migrating into the damaged heart tissues upregulate enzymatic machinery for degrading extracellular ATP and NAD to adenosine (Borg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A significant number of studies have been recently published evidencing about an important role played by the receptors for extracellular ATP and its metabolites as well as enzymes involved in regulating their metabolism in vascular and heart valve calcification (Fish et al, 2013; Towler, 2017; Dou et al, 2018; Golovkin et al, 2018; Kaniewska-Bednarczuk et al, 2018). Previously, it was shown that various receptor isotypes specific to extracellular adenosine (P1 family) and ATP (Р2Х and Р2Y families) were found on smooth muscle cells, the major cell type involved in formation of calcium depositions in the vascular wall (Fish et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Растущие и регенерирующие ткани, а также ткани с высоким уровнем клеточного оборота характеризуются продукцией различных ростовых и трансформирующих рост факторов, аденозина, адреномедуллина, проадреномедуллина, метаболических цитокинов (например, FGF-21) и других медиаторов, препятствующих развитию инсулинорезистентности (в факультативно гликолизирующих тканях) и выраженной провоспалительной активности клеток [1,62,83,146]. По мере прогрессирования тканевого стресса продукция этих медиаторов может возрастать, но уже на фоне доминирующей роли провоспалительных цитокинов [83,229].…”
Section: Sr в обеспечении пролиферации клеток и тканевого ростаunclassified
“…One of the most important mechanisms of suppression of inflammation, which is realized by Treg both in lymphoid tissue and in the site of inflammation, is the degradation of pro-inflammatory extracellular ATP to adenosine, which has a wide spectrum of antiinflammatory action and acts on the effector cells of innate and acquired immunity [8]. When comparing CD39 + and CD39 -Treg in vitro, it was shown that the presence of CD39 is closely related to the high ability of these cells to show their suppressor properties due to the efficient expression of the transcription factor FoxP3, as well as the regulatory molecules CTLA4, GARP, and LAP [28].…”
Section: Expression Of Cd39 and Cd73 By Various Subpopulations Of Regmentioning
confidence: 99%